Finite Element Analysis of Rear Underrun Protection Device during - Zainal Badri, Muhammad Syaaban; Ismail, Al Emran (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The rear underrun protection devices (RUPDs) during collisions are the main subject of the abstract's finite element analysis. Heavy vehicles must have rear underrun protection devices installed in order to stop passenger cars from sliding beneath them in the event of a rear-end collision. RUPD designs that are poor frequently cause fatal injuries in such accidents. This analysis uses numerical simulations and experimental tests to assess the effectiveness of RUPDs. The review identifies areas for improvement and looks at different research techniques used to evaluate RUPDs during car-to-heavy truck rear impacts. Discussions also include crash velocities, various car frontal crash test scales, and the ability of various RUPD designs to absorb energy. It also can be concluded that the higher impact velocity, the higher reaction force. The best performance of the RUPD is the New Design which absorbed 12 kJ, 19 kJ, 30 kJ for 12.5 m/s, 15.0 m/s and 17.5 m/s respectively.